Incentive Fees: erfolgsabhängige Vergütungsmodelle deutscher Publikumsfonds - Norbert Kluß; Markus König; Heinz Cremers (Hochschule für Bankwirtschaft (HfB), 2003)
This paper analyzes the current use of incentive-fee-concepts for mutual funds in Germany. Following an empirical analysis about the relevance of these methods, the different methods of calculation and the influence of different parameters are described. Further on it explains the impacts of possible basis of assessment, the clearing period and the opportunities of carrying back the obtained performance from the investor's point of view.
urn:nbn:de:101:1-2008072110
Keywords: G11; G19; G21; G29; 330; Incentive Fee; Performance Fee